AN IN-DEPTH LEARNING APPROACH: A CASE STUDY IN A FACULTY OF EDUCATION IN TANGERANG, INDONESIA [PENDEKATAN PEMBELAJARAN MENDALAM: STUDI KASUS DI FAKULTAS PENDIDIKAN DI TANGERANG, INDONESIA] - Zendrato, Juniriang (Polyglot, 2025)
Christian schools in Indonesia are expanding rapidly, necessitating a need for more skilled and qualified Christian teachers. Therefore, the research, which applies the qualitative approach with case study procedures, aims to offer an in-depth learning approach as a solution to provide reflective, responsive and responsible Christian teachers for Indonesia. The data gathered were course outlines, assessments, class activity photos, and student work. The result was that the in-depth learning approach was implemented by the Faculty of Education in Tangerang, Indonesia. It was shown by its teaching learning, which emphasized meaning making; challenged critical thinking, integrated faith and knowledge, as well as practiced problem solving. To make in-depth learning approach sustained in the future, the Faculty of Education must incorporate strategies such as negotiating power relations, creating a meaningful curriculum, fostering a culture of reflection, providing opportunities to explore new ideas and concepts, challenging traditional power dynamics, and transforming digital classrooms. For further research, conducting interviews and observations with students from the Faculty of Education is recommended to assess the impact of in-depth learning implementation. Abstrak bahasa Indonesia Sekolah kristen di indonesia berkembang pesat, sehingga kebutuhan akan guru Kristen yang terampil dan berkualitas semakin meningkat. Oleh karena itu, penelitian ini, yang menggunakan pendekatan kualitatif dengan prosedur studi kasus, bertujuan menawarkan pendekatan pembelajaran yang mendalam sebagai solusi untuk menghasilkan guru Kristen yang reflektif, responsif, dan bertanggung jawab bagi Indonesia. Data yang dikumpulkan meliputi silabus mata kuliah, penilaian, foto aktivitas kelas, dan hasil karya mahasiswa. Hasilnya menunjukkan bahwa pendekatan pembelajaran yang mendalam telah diterapkan oleh Fakultas Pendidikan di Tangerang, Indonesia. Hal ini terlihat dari proses pembelajaran yang menekankan pada pembentukan makna, menantang kemampuan berpikir kritis, mengintegrasikan iman dan pengetahuan, serta mempraktikkan penyelesaian masalah. Untuk menjaga keberlanjutan pendekatan pembelajaran mendalam di masa depan, Fakultas Pendidikan perlu menerapkan strategi seperti: negosiasi dalam hubungan kekuasaan, menciptakan kurikulum yang bermakna, mendorong budaya refleksi, memberikan kesempatan untuk mengeksplorasi ide dan konsep baru, menantang dinamika kekuasaan tradisional, dan mentransformasi ruang kelas digital. Untuk penelitian selanjutnya, disarankan untuk melakukan wawancara dan observasi terhadap mahasiswa Fakultas Pendidikan guna menilai dampak penerapan pendekatan pembelajaran mendalam.